SIMULATION TECHNIQUE TO BRIDGE THE GAP IN PSYCHIATRIC NURSING - Ramachandra; A Bhaskar; D Mythili; P Vijayalakshmi (Indian Journal of Psychiatric Nursing)
Availability of Simulation Technique to bridge the gap in Psychiatric Nursing affords an excellent opportunity to provide increased facility for training the student nurses. This is extremely relevant since in the last decade there has been an increase in the member of nursing colleges in India, to meet the demand for nursing staff. This expansion offers several challenges in providing opportunities for bedside clinical teaching. It is in this context, simulation technique has been found to be very helpful in offering training to the nursing students, so that, they get equipped adequately to meet the challenges encountered when they are posted for duty in clinical settings.